Corporate Social Responsibility in Asia Practice and Experience - Low, Kim Cheng Patrick; Idowu, Samuel O.; Ang, Sik Liong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book presents a rich collection of research studies on the theory and practice of CSR in Asia. It includes valuable contributions of practice-oriented researchers from various Asian countries such as Brunei, China, India, Indonesia, Japan, Korea, Malaysia, and Singapore, and from several non-Asian countries, such as Australia, Canada and the USA. The book presents a comprehensive overview of the practice of CSR in Asia. Normally CSR is seen in the Western angles, but here, in this book, Asian philosophies and thoughts are also examined. Touted as the first of its kind, the book also compares Western and Asian perspectives on CSR and presents them in the light of Asian philosophies and thoughts, such as Confucian, Islamic (Koranic), Indian (Vedantic) and other Asian ways of looking at CSR in their own rights and perspectives.
Part One: East and South Asia -- Part Two: Brunei and South East Asia/United States of America -- Part Three: Pacific Asia.
Keywords: Economics; Regional economics; Economics/Management Science; Non-Profit Enterprises/Corporate Social Responsibility; Business Strategy/Leadership.; Regional/Spatial Science